Rising wages in Bangladesh - Zhang, Xiaobo; Rashid, Shahidur; Ahmad, Kaikaus; Mueller, Valerie; Lee, Hak Lim; Lemma, Solomon; Belal, Saika; Ahmed, Akhter (International Food Policy Research Institute, 2013)
Using data from multiple sources, we show that in Bangladesh, the increase in real wages, particularly female wages, has accelerated since the late 2000s, suggesting that the Lewis turning point (the point at which the labor market starts to shift in favor of workers) has arrived in Bangladesh. Rising wages are likely a result of a combination of more ample job opportunities in the nonfarm sector, especially in the manufacturing sector for females, and a greater amount of remittances, primarily from male workers overseas. Since human capital is the most important asset for the poor, the escalation in real wages has boosted the poor’s earnings, thereby reducing their likelihood of being poor.